2015
DOI: 10.1186/s12889-015-1468-0
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behavior and vulnerability to HIV infection among seasonal migrant laborers in Metema district, northwest Ethiopia: a cross-sectional study

Abstract: BackgroundPoor socio-economic conditions fuel seasonal migration of adult males from Northwestern Ethiopia, but behavioral and other migration-related changes increase their vulnerability to HIV/AIDS. This study examined risky sexual behaviors and associated factors that may lead to increased HIV infection vulnerability among migrant laborers in Metema District, Ethiopia.MethodsA community-based cross-sectional study was conducted from July 8–18, 2013 at farms with migrant laborers. We enrolled 756 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 21 publications
3
54
2
1
Order By: Relevance
“…Districts with a higher proportion of migrants were statistically at greater risk for HIV infection. This finding could be explained in part by risky sexual behaviours, such as multiple sexual partners or low and inconsistent condom use, likely to increase vulnerability to HIV infection (Federal and Prevention, 2007;Tiruneh et al, 2015). Seasonal migration of labour in the study area, largely undertaken by younger individuals (mean age 28.4 years), also contributes to HIV transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Districts with a higher proportion of migrants were statistically at greater risk for HIV infection. This finding could be explained in part by risky sexual behaviours, such as multiple sexual partners or low and inconsistent condom use, likely to increase vulnerability to HIV infection (Federal and Prevention, 2007;Tiruneh et al, 2015). Seasonal migration of labour in the study area, largely undertaken by younger individuals (mean age 28.4 years), also contributes to HIV transmission.…”
Section: Discussionmentioning
confidence: 99%
“…These patterns delineate mobile youth in Rakai as a group at especially high risk of HIV. Previous research has demonstrated elevated HIV risk and risk behaviours among mobile populations, though largely among adults (Anglewicz, 2012; Bärnighausen et al, 2007; Brockerhoff & Biddlecom, 1999; Goldenberg et al, 2012; Kwena, Camlin, Shisanya, Mwanzo, & Bukusi, 2013; Tiruneh, Wasie, & Gonzalez, 2015; Zuma et al, 2003). Female migrants have been described as a particularly vulnerable group (Brockerhoff & Biddlecom, 1999; Camlin et al, 2014; Temin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, male and female in-migrants were more likely to report inconsistent condom use than non-migrants, but the opposite relationship was seen between travelers and non-travelers. Previous research has found high rates of inconsistent condom use among migrants in Africa (Brummer, 2002; Tiruneh et al, 2015) yet concurrently, migrant populations have been described as more knowledgeable about and perceptive of HIV risk than non-migrants (Brockerhoff & Biddlecom, 1999). It is possible that travelers in our study may have been more highly exposed to HIV prevention messaging and behaviours in their home communities, compared to migrants, and perceived themselves at high risk, which may influence condom use.…”
Section: Discussionmentioning
confidence: 99%
“…This sector is vulnerable to HIV due to its high dependence on human labour. Protracted morbidity and mortality are costing the industry financially, economically, and socially (including loss of skilled and experienced labour) [2]. The sector's vulnerability to the epidemic thus stems largely from vulnerabilities faced by workers employed in commercial agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that vulnerability of workers in commercial agriculture is rooted in the nature of work, which tends to be casual employment and largely based on migrant labour. In addition, poor living and working conditions on farms, coupled with limited access to health services and information about HIV increase vulnerability [2][3][4][5]. For agroestates to remain viable businesses, it is necessary and urgent to approach the epidemic with the seriousness it deserves.…”
Section: Introductionmentioning
confidence: 99%